IκB Kinase-Independent IκBα Degradation Pathway: Functional NF-κB Activity and Implications for Cancer Therapy - Tergaonkar, Vinay (American Society for Microbiology, 2003)
Antiapoptotic activity of NF-κB in tumors contributes to acquisition of resistance to chemotherapy. Degradation of IκB is a seminal step in activation of NF-κB. The IκB kinases, IKK1 and IKK2, have been implicated in both IκB degradation and subsequent modifications of NFκB. Using mouse embryo fibroblasts (MEFs) devoid of both IKK1 and IKK2 genes (IKK1/2(−/−)), we document a novel IκB degradation mechanism. We show that this degradation induced by a chemotherapeutic agent, doxorubicin (DoxR), does not require the classical serine 32 and 36 phosphorylation or the PEST domain of IκBα. Degradation of IκBα is partially blocked by phosphatidylinositol 3-kinase inhibitor LY294002 and is mediated by the proteasome. Free NF-κB generated by DoxR-induced IκB degradation in IKK1/2(−/−) cells is able to activate chromatin based NF-κB reporter gene and expression of the endogenous target gene, IκBα. These results also imply that modification of NF-κB by IKK1 or IKK2 either prior or subsequent to its release from IκB is not essential for NF-κB-mediated gene expression at least in response to DNA damage. In addition, DoxR-induced cell death in IKK1/2(−/−) MEFs is enhanced by simultaneous inhibition of NF-κB activation by blocking the proteasome activity. These results reveal an additional pathway of activating NF-κB during the course of anticancer therapy and provide a mechanistic basis for the observation that proteasome inhibitors could be used as adjuvants in chemotherapy.